OBSTETRIC HEMORRHAGE IN MATERNAL EMERGENCIES : RISK FACTORS, CLINICAL MANAGEMENT, AND PREVENTION STRATEGIES - Juita, Ratna; Simanullang, Ester; Panjaitan, Ruth Rosa Minanta; Alam, Selly Widya; Pasaribu, Riska Susanti (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Obstetric hemorrhage remains one of the most significant maternal emergencies and continues to be a leading cause of maternal morbidity and mortality worldwide. Despite advances in maternal healthcare, hemorrhage during pregnancy, childbirth, and the postpartum period remains a major challenge, particularly in low- and middle-income countries.This study aimed to review the current evidence on risk factors, clinical management, and prevention strategies for obstetric hemorrhage, with the goal of improving maternal health outcomes. A literature review was conducted using articles published between 2023 and 2025 retrieved from PubMed, Scopus, ScienceDirect, Google Scholar, and Wiley Online Library. Relevant studies discussing obstetric hemorrhage, maternal emergencies, risk factors, clinical management, and prevention strategies were selected and analyzed through thematic content analysis. The review found that postpartum hemorrhage is the most common form of obstetric hemorrhage and a major contributor to maternal mortality. Uterine atony was identified as the leading cause, followed by retained placenta, genital tract trauma, and coagulation disorders. Major risk factors included maternal anemia, advanced maternal age, multiparity, prolonged labor, cesarean section, placenta previa, and hypertensive disorders. Evidence-based interventions such as active management of the third stage of labor, uterotonic administration, tranexamic acid therapy, blood transfusion, and multidisciplinary emergency care significantly improved maternal outcomes. Most obstetric hemorrhage-related maternal deaths are preventable through early identification of risk factors, timely diagnosis, effective clinical management, and strengthened maternal healthcare systems.